Corn Bran As An Alternative To High-Fiber Snacks: Bekatul Jagung Sebagai Alternatif Kudapan Makanan Tinggi Serat - Putu Candriasih; Hermin Awusi; Laraswati Anggraini; Fahmi Hafid (Jurnal Pengabdian Masyarakat: Svasta Harena, 2022)
Fiber is one of the nutrients that has an important role in the body but the level of consumption is not paid attention to by the public. Along with the rapid progress of the times, it has had an impact on changes in the lifestyle of the Indonesian people, ranging from unhealthy eating patterns to lack of physical activity. The purpose of this community service is to provide information on the utilization of food waste into food with high fiber content and the development of corn bran biscuit products with kepok banana flour and increase mother's knowledge about the importance of fiber for the body. The method of this activity is through community education to help increase participants' information and understanding about the importance of fiber for our bodies. The results of this activity showed that there was an increase in participants' knowledge about the importance of fiber for our bodies. The percentage of participants with good knowledge category before attending the counseling was 60% (pre-test) and increased to 93.7% after attending the counseling (post-test). The conclusion of this activity is that corn bran can be processed into food sources of fiber. This activity was greeted with great enthusiasm and went smoothly, it is hoped that similar activities will be held in the future